KONSEP PERSEGI DAN PERSEGIPANJANG DALAM POLA PENGUBINAN SEBAGAI BENTUK ANALISIS NUMERASI SISWA BERKEMAMPUAN TINGGI DI KELAS IX - Lestari, Putri Budi; Hariastuti, Rachmaniah Mirza; Mutimmah, Dzurotul (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
Numeracy is the ability of students to understand and use mathematical concepts in everyday life. In general, numeracy can be done by students with high abilities because it requires in-depth analysis. This study was conducted qualitatively, and aimed to analyze and describe the numeracy of high-ability students in grade IX as a comparison with the AKM results that had been carried out in grade VIII. The study was conducted at SMPN 5 Banyuwangi with 3 subjects selected purposively. Data validation was carried out by triangulation of methods which were realized through tests and interviews. Data analysis was carried out qualitatively. The results of the study showed that the numeracy of high-ability subjects was still not optimal. This condition is known from the failure to achieve the indicator of predicting alternative problem-solving results. This opens up opportunities to develop students’ abilities in predicting alternative problem-solving in subsequent studies.